2017
DOI: 10.1016/j.ejphar.2017.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Licocoumarone isolated from Glycyrrhiza uralensis selectively alters LPS-induced inflammatory responses in RAW 264.7 macrophages

Abstract: The effects of licocoumarone (LC) isolated from Glycyrrhiza uralensis were studied in LPS-stimulated RAW 264.7 macrophages. Our study demonstrated that LC dose-dependently attenuated LPS-induced NO production by down-regulating iNOS expression. Additionally, the treatment with LC inhibited LPS-induced expression of cytokines including IL-1β, IL-6 and IL-10, but not TNF-α, at both mRNA and protein levels. Similar suppressive effects of LC were observed on LPS-stimulated murine peritoneal macrophages as well. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Accumulation of nitrite, a metabolite of NO in the culture media, was measured by Griess assay as previously reported [ 37 ]. Briefly, cells were stimulated with 100 ng/mL of LPS for 24 h in the presence of the test compounds (0–50 μM).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation of nitrite, a metabolite of NO in the culture media, was measured by Griess assay as previously reported [ 37 ]. Briefly, cells were stimulated with 100 ng/mL of LPS for 24 h in the presence of the test compounds (0–50 μM).…”
Section: Methodsmentioning
confidence: 99%
“…It has been known that activation of MAPKs (ERK1/2, p38, and JNK) is involved in modulating the NF-κB-regulated gene activation ( Wu et al, 2017 ) As shown in Figure 2E , 2′- O -GH significantly suppressed the LPS-induced phosphorylation of ERK1/2, p38, and JNK in a concentration-dependent manner. Furthermore, pretreatment with MAPK inhibitors (U0126, SP600125, and SB203580) suppressed the production of NO (Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 84%
“…Inflammation is a complex processes triggered by foreign pathogens or tissue injury to eliminate harmful stimuli as well as to initiate the healing and repair process of the damaged tissue ( Laveti et al, 2013 ). LPS is a major constituent of the cell wall of Gram-negative bacteria, which activates macrophages and induces inflammatory mediators and cytokines ( Mo et al, 2014 ; Wu et al, 2017 ). Overwhelming secretion of pro-inflammatory cytokines causes severe tissue damage, multiple organ failure, or death ( Ozer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe vera extract can downregulate TNF‐α, IL‐1β and IL‐6 expression in macrophages in a mouse model of lipopolysaccharide (LPS)‐induced acute lung injury (ALI), thus potentially protecting LPS‐induced ALI . Other extracts used in traditional Chinese medicine, such as curcumin, emodin, berberine and grass coumarone, have similar effects. Most of the traditional Chinese medications that inhibit tumours have “promoting blood stasis, reducing swelling and dispersing” effects.…”
Section: Exogenous Inducers Of Macrophage Heterogeneitymentioning
confidence: 99%